Analysis of Design Features of Fish Trawls and Shrimp Trawls of Thoothukkudi Coast - N., Neethiselvan; G., Brucelee (Fishery Technology, 2025)
The investigation deals with the comparison of body proportions of fish trawls and coastal shrimp trawls of Thoothukkudi coast with each other and with those of a standard FAO fish cum shrimp trawl. Significant variations could be noticed between fish trawls and coastal shrimp trawls of Thoothukkudi coast with respect to parameters viz. length of bottom wing, breadth of top bosum, breadth of bottom bosum, breadth and length of second belly as evidenced from low percentages of overlapping (<25%). The deviations observed in certain morphometric measurements of fish and coastal shrimp trawls from that of standard FAO fish cum shrimp trawl design stressed the need for improving the design features of the existing trawls of Thoothukkudi coast. The study suggested to increase the length of bottom wing and to reduce the belly breadth, belly depth, breadth of top and bottom bosum in fish trawls. Irrespective of the type, all trawls invariably had the cod end mesh size of 20mm. The study recommends fitting of square mesh panel of 30-mm mesh size in the cod end of fish and shrimp trawls of Thoothukkudi coast to exclude juvenile fishes.